2004
DOI: 10.1128/jcm.42.6.2694-2700.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Smear, Antigen Detection, and Nested-PCR Methods for Screening Refugees from Regions Where Malaria Is Endemic after a Malaria Outbreak in Quebec, Canada

Abstract: The importation of malaria into a region where it is not endemic raises many concerns, including the timely delivery of appropriate care, safety of the blood supply, and the risk of autochthonous transmission. There is presently no consensus on the best way to screen mobile populations for malaria. Between August 2000 and March 2001, 535 refugees arrived in Quebec, Canada, from Tanzanian camps. Within 4 weeks of resettlement of the first group of 224, the McGill University Centre for Tropical Diseases noted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 51 publications
3
89
0
2
Order By: Relevance
“…The result of this study indicated that the nested PCR protocol A was more efficacy and superior for detection of P. falciparum over protocol B. The detection limit of this protocol was good and similar as found in previous nested PCR studies [5,[23][24][25].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The result of this study indicated that the nested PCR protocol A was more efficacy and superior for detection of P. falciparum over protocol B. The detection limit of this protocol was good and similar as found in previous nested PCR studies [5,[23][24][25].…”
Section: Discussionsupporting
confidence: 63%
“…However, the limitations of microscopy are the requirement of skill and experience of the investigators. In addition, low sensitivity (100-200 parasites/μl of blood), time-consuming, and irregularity in species identification have been reported [5]. Hence, mixed infections have been found to misdiagnose.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies from Thailand, USA, Honduras and Colombia (22)(23)(24)(25) have shown sensitivities and specificities close to 100%, while one study from Canada (26) showed a sensitivity of 29.1 but a specificity of 95.6%.…”
Section: Discussionmentioning
confidence: 99%
“…ICT may also be used as an initial investigation in critically ill patients who are suspected to have malaria where the parasites may be sequestrated. Polymerase chain reaction based diagnosis of malaria although gives far better results is confined to few centres in India [17] . Cooke et al [11] 91.3 9 2 Gupta et al [9] 87.5 100 Palmer et al [12] 94 (P vivax) 100 88 (P falciparum) 99.9 This study 100 (P vivax) 100 96 (P falciparum) 100…”
Section: Discussionmentioning
confidence: 99%